PROFILE OF NEPHROLITHIASIS PATIENTS TREATED WITH MINI-PERCUTANEOUS NEPHROLITHOTOMY (MINI-PCNL): A SINGLE CENTER EXPERIENCE IN JAMBI, INDONESIA - Ingratoeboen, Wyckmell Octof; Herman, Hendra; Rachman, Wendi; Fauzan, Randy; Ardiansyah (Indonesian Journal of Urology, 2024)
Objective: This study aims to describe the characteristics of patients undergoing mini-PCNL at our center in Jambi, Indonesia. Material & Methods: This is a descriptive study involving patients with kidney stones treated with mini-PCNL during 2017 – 2021 in Jambi. The selection of the study subjects was using total sampling method. All patients had a medical history taken and a physical examination performed prior to surgery. The procedure was performed by three operators in one referral district hospital. Results: From 2017 to 2021, a total of 188 mini-PCNL procedures were performed at our center for the removal of kidney stones. However, only 186 cases were included in this study after excluding 2 due to incomplete data. The mean age of patients in this study was 49.3 years old (ranging from 12–87 years old) with the majority being male (101/165 [61.21%]). Of 186 cases, a total of 175 cases had no residual stone and only 11 had residual stone (stone-free rate [SFR] 94.08%). Most patients presented with hydronephrosis, and DJ stent placement was performed in 44 out of 186 cases. The SFR decreased as the stone size increased. Conclusion: Mini-PCNL proves to be a valuable choice for managing kidney stones, especially for medium-sized and hard stones, leading to enhanced patient results and reduced post-operative complications. Keywords: Kidney stone, mini-PCNL, stone free rate.